ISSUES OF IMPROVING THE CALCULATION OF INCOME TAX BENEFITS BASED ON FOREIGN EXPERIENCE AND REFORMS CARRIED OUT IN UZBEKISTAN - Professor., Usmanova Mukhlisa Sagdullayevna (Scholar Express Journals, 2023)
The article discusses issues of improving the calculation of income tax benefits based on foreign experience and reforms carried out in Uzbekistan.
Keywords: Tax credits; tax credit; tax holidays